2017
DOI: 10.1111/ijfs.13506
|View full text |Cite
|
Sign up to set email alerts
|

Influences of a natural colourant on colour and salty taste perception, liking, emotion and purchase intent: a case of mayonnaise‐based dipping sauces

Abstract: Summary Effects of colourant and a ‘natural source’ statement on sensory liking, emotion, saltiness expectation and purchase intent (PI) of three dipping sauces containing shrimp head colourant [no‐colourant (NC); moderate‐colourant (MC, 1.2% colourant); high‐colourant (HC, 3.6% colourant)] were evaluated. Consumers disliked colour of HC compared to MC (4.65 vs. 6.24). Despite the same NaCl level, saltiness liking decreased with increasing colourant [6.38 (NC), 5.43 (MC), 3.97 (HC)]. Correspondence analysis bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 33 publications
(80 reference statements)
2
23
0
Order By: Relevance
“…Both snacks and dipping sauces contain relatively high amounts of sodium. In our previous study, we observed positive relationships between visual colour cues and salty taste expectation (Sukkwai et al, 2017). However, the effects of the salt type (NaCl or KCl) and 'sodium content' claim have yet to be evaluated.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Both snacks and dipping sauces contain relatively high amounts of sodium. In our previous study, we observed positive relationships between visual colour cues and salty taste expectation (Sukkwai et al, 2017). However, the effects of the salt type (NaCl or KCl) and 'sodium content' claim have yet to be evaluated.…”
Section: Introductionmentioning
confidence: 90%
“…The percentage of salt (NaCl) added to the dipping sauce was to obtain comparable sodium content of the commercial dipping sauces (typically 200-280 mg Na per serving; Sukkwai et al, 2017). A total of nine samples were prepared with three colorant concentrations (NC = no colorant added, MC = moderate colorant added at 1.2% and HC = high colorant added at 3.6% w/w) and three salt type/content (regular salt, RS = 0.4% NaCl added; reduced sodium, ReS = 0.4% KCl added; and NS = no salt added).…”
Section: Preparation Of Dipping Sauces and Colour Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hedonic scores are one of the criteria to guide food product development for many years, sensory liking is no longer an efficient sole parameter to predict food choice in real life environments, whereas emotion responses have successfully differentiated equally liked products (Jiang, King, & Prinyawiwatkul, ). Recent studies have observed the relationship between sensory characteristics and emotion of food products such as coffee (Bhumiratana, Adhikari, & Chambers, ), mayonnaise‐based dipping sauces (Sukkwai et al., ; Sukkwai, Chonpracha, Kijroongrojana, & Prinyawiwatkul, ), gluten‐free muffin (Wardy et al., ), and peanut products (Pujols, Ardoin, Chaiya, Tuuri, & Prinyawiwatkul, ; Sukkhown, Pirak, Chonpracha, Ardoin, & Prinyawiwatkul, ). They found that differences in visual cues of the products affected consumer perception, liking, emotions, and PI.…”
Section: Introductionmentioning
confidence: 99%
“…Color influences consumer perceptions of flavor, liking, emotions, and overall perception and purchase intent . Chambers and Wolf suggested that ranking tests on visual evaluations might be less prone to fatigue than taste and aroma tests, possibly favoring a joint ranking (1SS) session.…”
Section: Introductionmentioning
confidence: 99%